The Re-emigration of American children living in Mexico - Cuecuecha-Mendoza, Alfredo; Lara-Lara, Jaime; Vázquez-Vázquez, José Dionicio (Papeles de Población; Vol. 23 Núm. 91 (2017), 2017)
This paper analyzes the situation of children born in the United States who reside in Mexico, with emphasis in their decisions to return to the United States with the purpose of joining the American educational system in a context of transnationalism. The results indicate that children born in the United States live in households with relatively educated head of households, but in which the paternal presence is low. These children have the same probability of attending school, but accumulate more years of schooling than comparable children born in Mexico. These children return to the United States in a high proportion at some point in his life, with a high probability of doing so with the aim of joining the American school system.